Turkish validity and reliability of the Sexual Complaints Screener for Women. Issue 4 (2nd October 2019) - Gündüz, Anıl; Kumru Bayazit, Rayka; Gündoğmuş, İbrahim; Sertçelik, Sencan; Gönül, Hatice; Yaşar, Alişan Burak; Oğuz, Gülay; Sungur, Mehmet Zihni
ABSTRACT: OBJECTIVE: The Sexual Complaints Screener for Women (SCS-W) is a brief, practical and up-to-date scale which assesses sexual problems parallel with the current diagnostic manuals. The SCS-W consists of 10 questions which assess a variety of sexual dysfunctions and potential distress experienced at the time of and the last six months leading to the evaluation. This study aims to assess the validity and reliability parameters of the Turkish version of the SCS-W. METHODS: Cross-sectional study included 352 women between the ages of 18 and 25 who voluntarily completed the survey, 316 of which were included in the analysis. Data was collected through specific questionnaires including the Female Sexual Function Index, the Short Form Health Survey (SF-36), the Turkish translation of SCS-W, and a sociodemographic form. The Cronbach Alpha Test was used to calculate the internal consistency and the Pearson Correlation Test was used for total score correlations as well as to determine cross-validity. An explanatory factor analysis was applied to identify the validity of the scale. RESULTS: The average age of participants in the study was 21.17 ± 1.87. The Cronbach alpha internal consistency coefficient of the scale was 0.895, and the correlation coefficient for most of the items was found to be higher than 0.50. Correlation analysis between the SCS-W and the FSFI total score and subscales were statistically significant. CONCLUSION: The SCS-W has credible psychometric values for validity and reliability to screen and evaluate sexual complaints. To sum up, the SCS-W is a practical assessment tool with the considerable advantages of delivering cost-effective evaluation of female sexual problems in clinical settings, research, and daily practice.